The Effect of Thermal Contact Conductance (TCC) Between Aggregate Inclusion and Matrix on Thermal Conductivity of Cement-Based Material - Mom, Sokvisal; Hoeun, Sela; Bernard, Fabrice; Kamali-Bernard, Siham; Han, Virak (International Journal of Integrated Engineering, 2022)
The effect of Thermal Contact Conductance (TCC) on thermal conductivity of mortar has been studied at the interface between the limestone and cement paste. A novel methodology, which involves the use of Scanning Electron Microscope (SEM) to scan the image of the interface in mortar, the software PlotDigitizer to create a set of points of the interface, and the FE software Abaqus/CAE to perform heat transfer simulation, is proposed in this study. Moreover, several hypotheses at the interface such as the gaps, flaws, and Interfacial Transition Zone (ITZ) are also highlighted. Temperature drop, thermal conductivity, and the TCC coefficient has been calculated for each model in order to understand the effect of TCC on cement-based materials thermal properties. The results show that the temperature drops at the interface are very low and the TCC coefficients are very high so that it can be ignored in heat transfer simulation except for a large air gap at the interface. Thus, it can be concluded that the TCC has no influence on the thermal conductivity of mortar.